2012
DOI: 10.1002/jms.2987
|View full text |Cite
|
Sign up to set email alerts
|

An online nano‐LC‐ESI‐FTICR‐MS method for comprehensive characterization of endogenous fragments from amyloid β and amyloid precursor protein in human and cat cerebrospinal fluid

Abstract: Amyloid precursor protein (APP) is the precursor protein to amyloid β (Aβ), the main constituent of senile plaques in Alzheimer's disease (AD). Endogenous Aβ peptides reflect the APP processing, and greater knowledge of different APP degradation pathways is important to understand the mechanism underlying AD pathology. When one analyzes longer Aβ peptides by low-energy collision-induced dissociation tandem mass spectrometry (MS/MS), mainly long b-fragments are observed, limiting the possibility to determine va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 46 publications
0
61
0
Order By: Relevance
“…106 It was used to identify novel α-synuclein isoforms in brain tissue and amyloid-β in cerebral spinal fluid. [107][108][109] These results demonstrated the utility of MS for structural studies. These proteins have been shown to have varied posttranslational modifications, which have been detected and characterized by mass spectrometry.…”
Section: Mass Spectrometry and Small Molecule-based Study Of Other Prmentioning
confidence: 60%
“…106 It was used to identify novel α-synuclein isoforms in brain tissue and amyloid-β in cerebral spinal fluid. [107][108][109] These results demonstrated the utility of MS for structural studies. These proteins have been shown to have varied posttranslational modifications, which have been detected and characterized by mass spectrometry.…”
Section: Mass Spectrometry and Small Molecule-based Study Of Other Prmentioning
confidence: 60%
“…Kituzame et al showed that one additional O-glycan is present in the longer splice variant, APP770, in COS cells [26]. Several additional O-glycosylation sites in APP have recently been identified in human-derived CSF: Ser597, Ser606, Ser611, Thr616, Thr634, Thr635, Ser662, and Ser680 (numbering as in the canonical sequence, APP770, without the signal peptide) [27,28]. The roles of these O-glycans are elusive, although it has been proposed that APP processing by a-secretase, b-secretase and c-secretase occurs after O-glycosylation of APP, and that O-glycosylated APP is preferentially secreted [26,29].…”
Section: App and Glycosylationmentioning
confidence: 99%
“…Deletion of the glycan domain of APP as well as treatment of hippocampal neurons with tunicamycin [79] indicate that N-glycans are required for the proper axonal sorting and the secretion of APP [80]. The O-glycosylation of APP has also been reported to be important in the function of APP by several authors [81][82][83][84][85][86][87][88]. We found that APP is modified with sialylated O-glycans in brain endothelial cells and that the modified APP is preferentially cleaved and secreted [86], indicating that APP O-glycosylation regulates the APP processing.…”
Section: The Role Of Protein Glycosylation In Admentioning
confidence: 98%